ANTAGONISTIC BACTERIA AGAINST SCHIZOPHYLLUM COMMUNE FR. IN PENINSULAR MALAYSIA - ANTARJO DIKIN; KAMARUZAMAN SIJAM; JUGAH KADIR; IDRIS ABU SEMAN (SEAMEO BIOTROP, 2006)
Schizophyllum commune Fr., is one of the important fungi, causes brown germ and seed rot of oil palm. Biodiversity of antagonistic bacteria from oil palm plantations in Peninsular Malaysia is expected to support in development of biopesticide. Isolation with liquid assay and screening antagonistic bacteria using dual culture assay were carried out in the bioexploration. A total of 265 bacterial isolates from plant parts of oil palm screened 52 antagonistic bacterial isolates against 5. commune. Bacterial isolates were identified by using Biolog* Identification System i.e. Bacillus macroccanus, B. thermoglucosidasius, Burkholderia cepacia, B. gladioli, B. multivorans, B pyrrocinia, B. spinosa, Corynebacterium agropyri, C. misitidis, Enterobacter aerogenes, Microbacterium testaceum, Pseudomonas aeruginosa, P. citronellolis, Rhodococcus rhodochrous, Serratia ficaria, Serratia sp., S. marcescens, Staphylococcus sciuri, Sternotrophomonas maltophilia.Key words : Schizophyllum commune, biodiversity, antagonistic bacteria